The FAR Model: Evaluating the Quality of English Subtitling in Minion 2 The Rise of GRU Trailer Movie - Aulia Nisa Khusnia; Ruda Widagsa2 (Universitas Muhammadiyah Malang, 2025)
The FAR method rates subtitle quality in three categories: functional equivalency (do the subtitles accurately reflect the speaker's meaning), acceptability (do the subtitles sound natural and correct in the target language), and readability (can the subtitles be read smoothly and without interruption). The FAR model is error-based and contains a penalty score system that allows the examiner to indicate which areas won't work, making it effective for instruction and criticism. The information is taken from the subtitles of an English-Indonesian Minion 2 thriller film. The film has a running time of 3 minutes and 19 seconds and was released on July 1, 2022. It was discovered that functional equivalence, acceptability, and readability were all present. Semantic and stylistic faults are subcategories of functional equivalencies.